Exploring Subtitling Strategies and Pronoun Translation in “Sang Pemimpi” (The Dreamer) Movie Subtitle - Sholihah, Nanda; Prihantoro, Prihantoro (Journal of Language and Literature, 2024)
The study of pronoun translation in subtitle is crucial to give insight for subtitler for maintaining the producing accurate, respectful, and culturally sensitive translations, ensuring effective communication across different languages and cultures. This research aims to identify pronoun translation in the Indonesian-English movie subtitle of Sang Pemimpi (The Dreamer) movie. This study was designed as qualitative research, with content analysis as a method of collecting the data. The analysis focused on how the pronoun in the subtitle translated from SL to TL, what are the cultural reasons of using pronoun and what are strategies used by the translator with considering grammatical and socio-cultural aspects in both the Source Language (SL) and Target Language (TL). The findings reveal three categories of pronoun translation occur in subtitle, they are pronoun to pronoun, pronoun to reference, and pronoun to omission. A total of 680 pronouns were translated, with 521 (77%) translated as pronoun to pronoun, 152 (22%) as a pronoun to omission, and 7 (1%) as a pronoun to reference. These results underscore the diverse background factors influencing why pronouns are translated, including socio-cultural and grammatical considerations. There are several subtiling strategies used by translators to translate the sentences, including genralization, direct translation, explicitation, and subtiution. These strategiess are employed to ensure fidelity to the original meaning while adapting to linguistic and cultural nuances in the target language.